2016
DOI: 10.3389/fcimb.2015.00102
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Approach to Reveal Putative Host-Derived Biomarkers of Periodontitis by Network Topology Characterization of MMP-REDOX/NO and Apoptosis Integrated Pathways

Abstract: Periodontitis, a formidable global health burden, is a common chronic disease that destroys tooth-supporting tissues. Biomarkers of the early phase of this progressive disease are of utmost importance for global health. In this context, saliva represents a non-invasive biosample. By using systems biology tools, we aimed to (1) identify an integrated interactome between matrix metalloproteinase (MMP)-REDOX/nitric oxide (NO) and apoptosis upstream pathways of periodontal inflammation, and (2) characterize the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Specific host-or bacteria-derived biomarkers detected in saliva indicate the presence or progression/remission of periodontitis. With the aid of Omics Technologies, search for biomarkers with high sensitivity and specificity has broadened during the last decade [2]. The use of a single salivary marker in detection of periodontitis is, however, challenged by the episodic and multi-factorial characteristics of the disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Specific host-or bacteria-derived biomarkers detected in saliva indicate the presence or progression/remission of periodontitis. With the aid of Omics Technologies, search for biomarkers with high sensitivity and specificity has broadened during the last decade [2]. The use of a single salivary marker in detection of periodontitis is, however, challenged by the episodic and multi-factorial characteristics of the disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 32 network properties were calculated and adopted in subsequent analysis. These properties were popular for analyzing a complex biological network, which included: (1) Average Closeness Centrality : the average number of steps required to reach the studied node from any node in a network (Ma et al, 2016 ); (2) Average Shortest Path Length : the average length of shortest paths between the studied node and all other ones (Zhang et al, 2014 ); (3) Betweenness Centrality : the number of times the studied node serving as a linking bridge along shortest path between any two nodes (Zeidán-Chuliá et al, 2015 ); (4) Bridging Centrality : the product of the bridging coefficient and betweenness centrality (Hwang et al, 2008 ); (5) Bridging Coefficient : the extent of the studied node lying between any other densely connected nodes in the network (Paladugu et al, 2008 ); (6) Closeness Centrality Sum : the reciprocal of the sum of the shortest paths between the studied node and all other nodes in the network (Costenbader and ValenteFontanesi, 2003 ); (7) Clustering Coefficient : the number of the connected pairs between all neighbors of node (Watts and Strogatz, 1998 ); (8) Current Flow Betweenness : a centrality index measuring the level of information travels along all possible paths within network (Paladugu et al, 2008 ); (9) Current Flow Closeness : the variant of current flow betweenness (Zhang et al, 2017b ); (10) Degree : the number of edges linked to a node (Braeuning, 2013 ); (11) Degree Centrality : the number of links incident upon a studied node (Batool and Niazi, 2014 ); (12) Deviation : the variation between sum of node distances and network unipolarity (Zhang et al, 2017a ); (13) Distance Deviation : the absolute difference between nodes' distance sum and network's average distance (Rogelj et al, 2013 ); (14) Distance Sum : the sum of all shortest paths starting from the studied node (Bolser et al, 2003 ); (15) Eccentric : the absolute difference between nodes' eccentricities and network's average eccentricity (Zhang et al, 2017a ); (16) Eccentricity : the maximum non-infinite shortest path length between the studied node and all other nodes in the network (Bolser et al, 2003 ); (17) Eccentricity Centrality : the largest geodesic distance between the node and any other node (Batool and Niazi, 2014 ); (18) Eigenvector Centrality : the sum of its neighbors' centrality values (Solá et al, 2013 ); (19) Harmonic Closeness Centrality : the sum of the reciprocals of the average shortest path lengths of each node in network (Zhang et al, 2017b ); (20) Interconnectivity : a connectivity index indicating the quality of the studied nodes being connected together (Emig et al, 2013 ); (21) Load Centrality : the fraction of all th...…”
Section: Methodsmentioning
confidence: 99%
“…It indicated that those nodes are key points which control the communication with other nodes in CePIN. Were they removed, the network would be divided into fragments [53]. All nodes with high values of betweenness over threshold are named as “bottlenecks” [54].…”
Section: Methodsmentioning
confidence: 99%